A behavioral comparison of the common laboratory rat strains Lister Hooded, Lewis, Fischer 344 and Wistar in an automated homecage system. (4th November 2013) - Clemens, L. E.; Jansson, E. K. H.; Portal, E.; Riess, O.; Nguyen, H. P.
Abstract Behavioral characterization is an important part of establishing novel animal models, but classical behavioral tests struggle to reveal conclusive results due to problems with both reproducibility and validity. On the contrary, automated homecage observations are believed to produce robust outcomes that relate more to natural animal behavior. However, information on the behavior of background strains from such observations, which could provide important reference material, is rare. For this reason, we compared the behavior of the commonly used Lister Hooded, Lewis, Fischer 344 and Wistar rats during 70 h of exposure to an automated homecage system at 2, 4 and 6 months of age. We found considerable strain differences in metabolic parameters, novelty‐induced and baseline activity‐related behavior as well as differences in the development of these parameters with age. The results are discussed in terms of advantages and disadvantages of the system compared to classical behavioral tests, as well as the system's ability to recreate common findings in literature.